2006
DOI: 10.1159/000093532
|View full text |Cite
|
Sign up to set email alerts
|

Association between Alcohol Intake and Domain-Specific Cognitive Function in Older Women

Abstract: Moderate levels of alcohol intake may be associated with better cognitive function; however, this relationship may vary between cognitive domains. Women, aged 65–80 years, enrolled in the Women’s Health Initiative (WHI) randomized clinical trials of hormone therapy, underwent annual standardized testing for global cognitive function through the ancillary WHI Memory Study (average follow-up of 4.5 years) and domain-specific cognitive function through the WHI Study of Cognitive Aging (average follow-up of 1.7 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 76 publications
3
20
0
1
Order By: Relevance
“…The majority of women reported light drinking regardless of diagnosis (66% without and 62% with alcohol abuse or dependence). Therefore, our fi ndings are consistent with other studies demonstrating few negative (and in some cases positive) effects of light alcohol consumption on cognition in midlife (Dufouil et al, 1997;Espeland et al, 2006;Leroi et al, 2002;Schinka et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The majority of women reported light drinking regardless of diagnosis (66% without and 62% with alcohol abuse or dependence). Therefore, our fi ndings are consistent with other studies demonstrating few negative (and in some cases positive) effects of light alcohol consumption on cognition in midlife (Dufouil et al, 1997;Espeland et al, 2006;Leroi et al, 2002;Schinka et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The administration of a complete neurocognitive assessment is important in the evaluation of the effects of alcohol on cognition because subtle differences may go undetected as a result of the use of a partial assessment (Davies et al, 2005;Espeland et al, 2006). For example, heavy drinking has been associated with frontal-lobe dysfunction (Davies et al, 2005;Fox et al, 2000), whereas light to moderate drinking is associated with better verbal knowledge and fl uency (Espeland et al, 2006). A complete neurocognitive assessment would allow investigation of domain-specifi c effects as a function of drinking severity.…”
mentioning
confidence: 99%
“…A comparable association was also reported in healthy women with some cognitive functions, especially those related to verbal knowledge and phonemic fluency (see [80] ). These studies all found at least a small protective effect against dementia with mild to moderate alcohol consumption, although the Eugeria Study found this effect disappeared when place of residence was entered into the regression model (persons in institutions are usually forbidden alcohol but commonly have dementia).…”
Section: Treatment Effectiveness Of Antioxidantssupporting
confidence: 80%
“…This improvement specifically encompasses baseline attention, processing speed, which is the ability to perform tasks requiring rapid visual scanning and mental processing of information, memory such as verbal knowledge or memory including immediate and delayed recall, recognition memory, figural memory and working memory, as well as motor speed. This has been observed for both men and women [62,[66][67][68][69]. Gross et al (2011) concluded that that the consumption of alcoholic beverages three to four times per week or low levels of drinks per week through midlife and into later life, confers the best cognitive outcomes in old age, as defined by wordfinding ability in late life, a measure of executive function [70].…”
Section: Relationship Of Alcoholic Beverages To Cognitive Function Anmentioning
confidence: 97%